HUBUNGAN SOSIODEMOGRAFI, TINGKAT PENGETAHUAN DAN SIKAP TERKAIT COVID-19 DENGAN TINGKAT KEPATUHANMELAKUKAN PROTOKOL KESEHATAN PADA IBU HAMIL DIPUSKESMAS SINDANG BARANG BOGOR BARAT TAHUN 2022 - Bella Adisya Kansha (2022)
COVID-19 is an infectious disease caused by SARS-CoV-2 andeasily transmitted to vulnerable groups such as pregnant women. The high rate of morbidity and mortality of pregnant women infected with COVID-19 with a relative risk of 3.46 in 18 countries including Indonesia is caused by a decrease in immunity during pregnancy so compliance towards prevention of COVID-19 transmission through health protocols is required. Factors affecting compliance are sociodemographic factors such as age, education, income, knowledge and attitude. This study aims to determine the relationship of sociodemography, knowledge and attitudes related to COVID-19 with the level of compliance towards health protocols for pregnant women at the Sindang Barang Public Health Center, West Bogor in 2022. This research is an observational quantitative analytic study with Cross Sectional design and Consecutive Sampling on 42 respondents. The instrument is questionnaires. Univariate, bivariate and multivariate analysis are used. Based on chi-square test with a 95% confidence level, three variables, namely education level (p=0.024), income level (p=0.000) and attitude (p=0.000) have relationship to adherence of health protocols and two variables, namely age. (p=0.539) and knowledge (p=0.414) have no significant relationship. The multivariate test using multiple logistic regression results are the variable with strongest effect on adherence to health protocols was attitude (OR=13,461) followed by income level (OR=8,982) meaning the more positive the attitude and the higher the income, pregnant women will be more obedient to COVID-19 health protocol, while education level is a confounding variable that affects other variables so it needs to be controlled